Cx58 is associated with the metastasis of non-small cell lung cancer via MEF2B/Cx58 axis - Tan Fen; Chen Juan; Sun Lunquan; Zhang Lu; Zhou Rui (Acta Biochimica et Biophysica Sinica)
Connexins (Cxs), also known as gap junction proteins, are structurally related transmembrane proteins and have been implicated in carcinogenesis. Although some evidence suggests that these proteins are tumor suppressors due to their reduced expression in cancers, recent research indicates their complicated roles in tumor progression during different stages, including metastasis. Here, we show that Cx58, which is upregulated in non-small cell lung cancer (NSCLC), is modulated by myocyte-enhancer binding factor 2B (MEF2B). Either Cx58 or MEF2B knockdown attenuates the migration and invasion of NSCLC cells by inducing cytoskeleton rearrangement. Additionally, the prometastatic role of Cx58 in NSCLC is demonstrated in vivo. In conclusion, our findings suggest that Cx58 is transcriptionally activated by MEF2B and is involved in the metastasis of NSCLC by regulating cytoskeleton organization. Targeting the MEF2B/Cx58 axis may be exploited as a modality for improving NSCLC therapy.